2006
DOI: 10.1111/j.1471-4159.2006.04011.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the cellular prion protein affects the Ca2+ homeostasis in hippocampal CA1 neurons

Abstract: involved in the transport of the a1 subunit to the plasma membrane, was found to be up-regulated in knock out hippocampal tissue. On mRNA level however, no differences could be detected for the a1C, D and b2-4 subunits. In conclusion our data support the notion that lack of PrP C.does not directly affect the potassium channels underlying sI AHP , but modulates these channels due to its effect on the intracellular free Ca 2+ concentration via a reduced Ca 2+ influx through L-type VGCCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 57 publications
1
54
0
3
Order By: Relevance
“…In addition to the arrival of new immature granule cells, other PrP-dependent mechanisms may be altered in granule cells once migration is concluded. A reduced L-type Ca 2ϩ -channel expression, which was observed in PrP 0/0 granule cells in culture (Herms et al, 2000;Fuhrmann et al, 2006) (see also Korte et al, 2003), could reduce spike afterhyperpolarization by weakening activation of calcium-dependent K-channels (Colling et al, 1996;Herms et al, 2001) and contribute to alter repetitive spike discharge.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the arrival of new immature granule cells, other PrP-dependent mechanisms may be altered in granule cells once migration is concluded. A reduced L-type Ca 2ϩ -channel expression, which was observed in PrP 0/0 granule cells in culture (Herms et al, 2000;Fuhrmann et al, 2006) (see also Korte et al, 2003), could reduce spike afterhyperpolarization by weakening activation of calcium-dependent K-channels (Colling et al, 1996;Herms et al, 2001) and contribute to alter repetitive spike discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Toxic peptides of PrP have also been implicated in the alteration of Ca 2+ homeostasis thereby contributing to further ER stress (34). Loss of PrP may also contribute to the disruption of Ca 2+ homeostasis within neurons (35). Furthermore, overexpression of STCH in HEK293 cells sensitized them to tumor necrosis factor-related apoptosis-related ligand (TRAIL)-induced apoptosis, which was abolished by the stomach cancer-derived del223V-226L STCH mutation, which occurs within the ATPbinding domain (36).…”
Section: Discussionmentioning
confidence: 99%
“…For example, neurons from PrP-null mice have been reported to display various kinds of electrophysiological abnormalities (52)(53)(54)(55). It has been suggested that PrP C specifically suppresses the activity of a subclass of NMDA-type glutamate receptors based on the demonstration that PrP C physically interacts with the NR2D subunit of these receptors and the fact that neurons from Prn-p Ϫ/Ϫ mice showed enhanced NMDA-evoked currents and were more susceptible to glutamate-induced excitotoxic death (56).…”
Section: Biophysical Characteristics and Molecular Basis Of ⌬Cr Prp-imentioning
confidence: 99%